Non-LTE LINE FORMATION FOR S I - Korotin, S. A. (Одеські астрономічні публікації, 2008)
A comprehensive model atom for non-LTE line formation calculations for neutral sulfur in the spectra of F-K stars is presented. All the calculations were made using the 65-level atomic model of S I and Kurucz's atmosphere models with Teff = 5000 ÷ 6500 K, log g = 2 ÷ 4 and [Fe/H] = -4 ÷ 0. It was found that the lines of different multiplets are differently sensitive to the NLTE effects. The NLTE corrections themselves are quite small (about -0.1 dex) for the lines 6543-6557 Å they increase up to -0.26 dex for 8694 Å line, and achieve -1.1 dex for IR triplet 9212-9237 Å. The atomic model adequacy was checked by modeling of the sulfur lines that belong to the investigated multiplets in the solar spectrum, as well as in the spectra of two main sequence and two giant stars. Good fit between calculated and observed profiles is obtained. It was showed that the rather high sulfur overabundance found in some metal-deficient stars can be explained as a result of neglecting of the strong NLTE effects.